An Examination of the Ability of First Graders from the Science Curriculum Improvement Study Program to Describe an Object By Its Properties. - Allen, Leslie R. (Science Education)
The article presents an examination of the ability of first graders from the Science Curriculum Improvement Study (SCIS) Program to describe an object by its properties. According to the author, the child is taught to recognize material objects in the environment and distinguish the objects from its properties and the properties of an object from the uses to which the object is put and from the material of which it is made. Results of the study indicates that SCIS children appear to be able to apply to a new situation specific property words learned in the classroom. Finally, superior performance of SCIS children in the use of property words and a performance little or no better than the control group for other property words, suggests the possibility of improving proficiency in the area.